Menumbuhkan Nilai Karakter Anak melalui Film Anak Ruby Rainbow di Kelas II MI Gampong Meutia Langsa - restela, rika; Megawati, Putri (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2023)
Animated films have the advantage of being an alternative learning medium that instills character values in children. The ideal criteria for animated films include ease of understanding, simplicity, effective storytelling, the use of polite language, entertainment through engaging games, and the delivery of values easily accepted by children. One animated film that meets these criteria is